Mobility overestimation due to gated contacts in organic field-effect transistors - Emily G. Bittle (Nature Portfolio, 2016)
Charge mobility, extracted from current–voltage curves, is an important parameter for evaluating the performance of organic field-effect transistors. Bittle et al. show that charge mobility can be overestimated by one order of magnitude due to the gate bias dependence of the charge injection process.